The Economic Translation of Paradigm-Changing Innovation: A Short History of Biotechnology - A. Vertès, Alain (Technology Transfer and Entrepreneurship (Discontinued), 2016)
Exploiting scientific and technical breakthroughs is notoriously synonymous to an extremely challenging journey as it typically requires breaking free from established consensuses and models. A first step in the creation of novel economic activity is to recognise the paradigm-changing fundamentals of a new radical innovation, to identify the portfolio of products or services that could be derived from the new advances, and to bundle the relevant patents both for the purposes of ensuring freedom-to-operate as well as of securing the time-limited market exclusivity that composition-ofmatter patent claims bring. A second step is to access the required financial and human resources, and to generate the initial data that establish the proof-of-concept basis required to secure the further financial resources needed for reaching the next step in the venture creation process. A third step for the nascent company is to attract larger partners with competences in manufacturing, selling, and incrementally improving the new products. In the pharmaceutical industry, the last successful deployment of a radical innovation has been the coming of age of monoclonal antibodies. The emergence of novel paradigm-changing product spaces have since accelerated with novel product candidate classes including therapeutic stem cells, chimeric antigen receptor T-cells, or therapeutic nucleic acids such as siRNA, miRNA, or aptamers and gene therapies. In the chemical industry, the last radical innovation, which still needs to deeply permeate the industry, has been that of biofuels and sustainable chemicals including commodity chemicals and innovative polymers. Historic reviews of the cases of therapeutic antibodies and of biofuels are presented here highlighting the major trends and steps that enable the creation of novel economic activities from the transfer of academic discoveries.
Keywords: miRNA